Human Phase 1 trial of low-dose inactivated seasonal influenza vaccine formulated with Advax™ delta inulin adjuvant. Issue 33 (19th July 2016) - Gordon, David L.; Sajkov, Dimitar; Honda-Okubo, Yoshikazu; Wilks, Samuel H.; Aban, Malet; Barr, Ian G.; Petrovsky, Nikolai
Highlights: First-in-man study of seasonal influenza vaccine containing Advax delta inulin-based adjuvant. Advax adjuvant was safe and well tolerated. Advax adjuvant enabled up to 10-fold antigen dose-sparing. First use of antibody landscapes to compare adjuvanted and unadjuvanted vaccine groups. Abstract: Influenza vaccines are usually non-adjuvanted but addition of adjuvant may improve immunogenicity and permit dose-sparing, critical for vaccine supply in the event of an influenza pandemic. The aim of this first-in-man study was to determine the effect of delta inulin adjuvant on the safety and immunogenicity of a reduced dose seasonal influenza vaccine. Healthy male and female adults aged 18–65 years were recruited to participate in a randomized controlled study to compare the safety, tolerability and immunogenicity of a reduced-dose 2007 Southern Hemisphere trivalent inactivated influenza vaccine formulated with Advax™ delta inulin adjuvant (LTIV + Adj) when compared to a full-dose of the standard TIV vaccine which does not contain an adjuvant. LTIV + Adj provided equivalent immunogenicity to standard TIV vaccine as assessed by hemagglutination inhibition (HI) assays against each vaccine strain as well as against a number of heterosubtypic strains. HI responses were sustained at 3 months post-immunisation in both groups. Antibody landscapes against a large panel of H3N2 influenza viruses showed distinct age effects whereby subjects over 40 years old had a bimodal baseline HI distribution pattern, with the highest HI titers against the very oldest H3N2 isolates and with a second HI peak against influenza isolates from the last 5–10 years. By contrast, subjects >40 years had a unimodal baseline HI distribution with peak recognition of H3N2 isolates from approximately 20 years ago. The reduced dose TIV vaccine containing Advax adjuvant was well tolerated and no safety issues were identified. Hence, delta inulin may be a useful adjuvant for use in seasonal or pandemic influenza vaccines. Australia New Zealand Clinical Trial Registry: ACTRN12607000599471